Biochar composts and composites. (1st June 2015) - Ekebafe, Marian Osazoduwa; Ekebafe, Lawrence Olu; Ugbesia, Stella Omozee
Research has shown that the carbon content of wastes decreases during composting with an increase in the nitrogen content. This indicates that the increased microbial activity in the process results in an increased mineralisation rate of organic nitrogen. A formula containing biochar in the form of terra preta, biochar bokashi, biochar glomalin, biochar hydrogel and biochar mokusaku-eki could further enhance the stability of the system and its effectiveness as a soil ameliorant. It could increase the cation exchange capacity, reuse crop residue, reduce runoff, reduce watering, reduce the quantity of fertiliser, increase crop yield, build and multiply soil biodiversity, strengthen and rebuild our soil food web, sequester atmospheric carbon in a carbon negative process, increase soil pH, restructure poor soils, and reduce carbon dioxide/methane/nitrous oxide/ammonia emissions from gardens and fields. This paper considers these claims and also the wider environmental implications of the adoption of these processes. The intention of this overview is not just to summarise current knowledge of the subject, but also to identify gaps in knowledge that require further research.